Assessing post-abortion care using the WHO quality of care framework for maternal and newborn health: a cross-sectional study in two African hospitals in humanitarian settings - Estelle Pasquier; Onikepe O. Owolabi; Bill Powell; Tamara Fetters; Richard Norbert Ngbale; Daphne Lagrou; Claire Fotheringham; Catrin Schulte-Hillen; Huiwu Chen; Timothy Williams; Ann M. Moore; Mariette Claudia Adame Gbanzi; et al. (BMC, 2024)
Abstract Background Abortion-related complications remain a main cause of maternal mortality. There is little evidence on the availability and quality of post-abortion care (PAC) in humanitarian settings. We assessed the quality of PAC in two hospitals supported by an international organization in Jigawa State (Nigeria) and Bangui (Central African Republic, CAR). Methods We mapped indicators corresponding to the eleven domains of the WHO Maternal and Newborn Health quality-of-care framework to assess inputs, processes (provision and experience of care), and outcomes of PAC. We measured these indicators in four components of a cross-sectional multi-methods study: 1) an assessment of the hospitals' PAC signal functions, 2) a survey of the knowledge, attitudes, practices, and behavior of 140 Nigerian and 84 CAR clinicians providing PAC, 3) a prospective review of the medical records of 520 and 548 women presenting for abortion complications and, 4) a survey of 360 and 362 of these women who were hospitalized in the Nigerian and CAR hospitals, respectively. Results Among the total 27 PAC signal functions assessed, 25 were available in the Nigerian hospital and 26 in the CAR hospital. In both hospitals, less than 2.5% were treated with dilatation and sharp curettage. Over 80% of women received blood transfusion or curative antibiotics when indicated. However, antibiotics were given to about 30% of patients with no documented indication. Among discharged women in CAR, 99% received contraceptive counseling but only 39% did in Nigeria. Over 80% of women in Nigeria reported positive experiences of respect and preservation of dignity. Conversely, in CAR, 37% reported that their privacy was always respected during examination and 62% reported short or very short waiting time before seeing a health provider. In terms of communication, only 15% felt able to ask questions during treatment in both hospitals. The risk of abortion-near-miss happening ≥ 24h after presentation was 0.2% in Nigeria and 1.1% in CAR. Only 65% of women in the Nigerian hospital and 34% in the CAR hospital reported that the staff provided them best care all the time. Conclusion Our comprehensive assessment identified that these two hospitals in humanitarian settings provided lifesaving PAC. However, hospitals need to strengthen the patient-centered approach engaging patients in their own care and ensuring privacy, short waiting times and quality provider-patient communication. Health professionals would benefit from instituting antibiotic stewardships to prevent antibiotic-resistance.